ISLAMIC LAW VIEWS ON HARSH PHYSICAL PARENTING: A Comparative Study - Hasan, Mutia; Musyahid, Achmad; Wijaya, Abdi (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
This research aims to educate children in ordering prayers in Islam and then analyze it in the child protection law. However, in general, Islam places more emphasis on gentleness, patience, and compassion than on violent ways in educating children, although in some instances showing disbelief and opposing children's mistakes is necessary, of course, correctly and appropriately. In the concept of Islamic law, violence has become an enjoyable theme to discuss. On the one hand, there is a hadith from the Prophet about educating children, which, if understood textually, raises the public perception of the necessity of violence in educating children. The Child Protection Law aims to guarantee and protect children and their rights to live, grow, develop and participate optimally following human dignity and protection from violence and discrimination. Keywords: Islamic Law; Prayer; Child Protection Act